Kinetic analysis of the block start and first two contacts in sprinting - Graham-Smith, P.; Brandner, C.; Ryu, J. H.; Gallagher, L. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to examine the force production characteristics of the arms and each leg in the block start and in the first two contacts of the acceleration phase in sprinting. The set-up consisted of six force platforms embedded in an indoor running track. A total of 61 starts from 19 male international level athletes were collected during maximal effort starts and accelerations between 10m and 40m. The average time over 10m was 1.648 ±0.048 seconds, measured using a Laveg speed gun. Results indicated that the arms accounted for 13.9% of the vertical impulse and -2% to horizontal impulse, the front leg 69% and 60% and the rear leg 25 and 33% respectively. Peak vertical and horizontal forces (relative to BW) in the front leg and their associated RFD`s produced the strongest correlations with time over 10m (all p<0.001).